2003
DOI: 10.1097/00019501-200309000-00003
|View full text |Cite
|
Sign up to set email alerts
|

Serum tumour necrosis factor-??, interleukin-2 and interleukin-10 activation in stable angina and acute coronary syndromes

Abstract: When compared to stable CAD and healthy subjects, acute coronary syndromes are associated with long-term increase of serum concentrations of pro- and anti-inflammatory cytokines. It seems likely that sudden CAD progression leading to acute coronary syndromes is triggered/accompanied by prolonged immune activation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
49
2
9

Year Published

2006
2006
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(61 citation statements)
references
References 24 publications
1
49
2
9
Order By: Relevance
“…In contrast, IL-10 is an anti-inflammatory cytokine that can inhibit a broad array of inflammatory and immune responses. It has been reported that the levels of IL-10 are altered in ACS patients, but disappointedly, we failed to detect a difference in the IL-10 levels in the NSTACS patients (62)(63)(64)(65). This led to a reduced IL-10/TNF-␣ ratio in the patients with NSTACS compared with the CSA patients and the CPS controls.…”
Section: Treg Cells Rte-treg Cellscontrasting
confidence: 61%
“…In contrast, IL-10 is an anti-inflammatory cytokine that can inhibit a broad array of inflammatory and immune responses. It has been reported that the levels of IL-10 are altered in ACS patients, but disappointedly, we failed to detect a difference in the IL-10 levels in the NSTACS patients (62)(63)(64)(65). This led to a reduced IL-10/TNF-␣ ratio in the patients with NSTACS compared with the CSA patients and the CPS controls.…”
Section: Treg Cells Rte-treg Cellscontrasting
confidence: 61%
“…Furthermore, IL-10 transgenic mice showed reduced atherosclerosis, whereas IL-10-deficient mice exhibited increased early atherosclerotic lesion formation (193), illustrating the anti-atherogenic potential of IL-10. However, results from clinical studies are not consistent as some report higher IL-10 levels in patients with ACS (133,183), whereas other report lower levels in patients with CAD (115) and unstable angina (256).…”
Section: Adipokines With a Tight Link To Cardiovascular Diseasementioning
confidence: 95%
“…Interleukin-6 (IL-6) was the first cytokine reported to be elevated in patient with unstable angina, and the degree of elevation correlated with the patients subsequent clinical outcome. Interleukin-1ß (IL-1ß) and tumor-necrosis-factor-a (TNF-a) are well-characterized proinflammatory cytokines with demonstrated roles in the progression of atherosclerosis [3][4][5][6][7][8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%